What is Behaviour? And (when) is Language Behaviour? A Metatheoretical Definition. (18th February 2016) - Uher, Jana
Abstract: Behaviour is central to many fields, but metatheoretical definitions specifying the most basic assumptions about what is considered behaviour and what is not are largely lacking. This transdisciplinary research explores the challenges in defining behaviour, highlighting anthropocentric biases and a frequent lack of differentiation from physiological and psychical phenomena. To meet these challenges, the article elaborates a metatheoretical definition of behaviour that is applicable across disciplines and that allows behaviours to be differentiated from other kinds of phenomena. This definition is used to explore the phenomena of language and to scrutinise whether and under what conditions language can be considered behaviour and why. The metatheoretical concept of two different levels of meaning conveyed in human language is introduced, highlighting that language inherently relies on behaviours and that the content of what‐is‐being‐said, in and of itself, can constitute (interpersonal) behaviour under particular conditions. The analyses reveal the ways in which language meaningfully extends human's behavioural possibilities, pushing them far beyond anything enabled by non‐language behaviours. These novel metatheoretical concepts can complement and expand on existing theories about behaviour and language and contribute a novel piece of theoretical explanation regarding the crucial role that language has played in human evolution.